EKSPLORASI PERSEPSI MASYARAKAT TERKAIT KEBIJAKAN KENAIKAN TARIF PPN, PPNBM 12 PERSEN, PKB TERHADAP DAYA BELI MOBIL - Oktaviana, Nikita; Sasanti, Elin Erlina (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.06.TAHUN.2025DO - 10.24843/EEB.2025.v14.i06.p12, 2025)
Tax is a mandatory contribution to the state that must be paid by individuals or bodies according to the law, without direct compensation, and is used for the benefit of the government in order to improve the welfare of the community. This study aims to collect opinions from one hundred people domiciled in Central Lombok Regency regarding the impact of the policy of increasing value added tax (X1) by 12 percent increasing sales tax on luxury goods (X2) by 12 percent, and progressive motor vehicle rates (X3) on the purchasing power of four-wheeled motor vehicles (Y). Value added tax (VAT) has a large and positive impact on consumer purchasing power. The subjects of this study were individuals who have an interest in paying motor vehicle tax in the Samsat Area of Central Lombok Regency. Data collection used primary data obtained through the distribution of questionnaires with the Purposive sampling method. The methodology for data analysis and processing used SmartPLS v4.1. The results of the study show that Value Added Tax (VAT), Luxury Goods Sales Tax (PPnBM), and Progressive Motor Vehicle Tax Rates (PKB) have a positive relationship and influence on the purchasing power of four-wheeled motor vehicles (cars).